Semi-Heyting Algebras Term-equivalent to Gödel Algebras - Abad, Manuel (2013)
In this paper we investigate those subvarieties of the variety SH of semi-Heyting algebras which are term-equivalent to the variety LH of Gödel algebras (linear Heyting algebras). We prove that the only other subvarieties with this property are the variety LCom of commutative semi-Heyting algebras and the variety L∨ generated by the chains in which a < b implies a → b = b. We also study the variety C generated within SH by LH, L∨ and LCom. In particular we prove that C is locally finite and we obtain a construction of the finitely generated free algebra in C.